2016
DOI: 10.3109/13880209.2016.1152277
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites of sevenHypericumspecies growing in Turkey

Abstract: Context The genus Hypericum (Hypericaceae) has attracted remarkable scientific interest as its members have yielded many bioactive compounds. Objective The current study presents investigations on the accumulation of hypericin, pseudohypericin, hyperforin, adhyperforin, chlorogenic acid, neochlorogenic acid, caffeic acid, 2,4-dihydroxybenzoic acid, 13,118-biapigenin, hyperoside, isoquercitrin, quercitrin, quercetin, avicularin, rutin, (+)-catechin and (-)-epicatechin in seven Hypericum (Hypericaceae) species g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Despite numerous studies and publications, Hypericum species are of high-priority research due to the increasing pharmacological significance and commercial value of Hyperici herba, officially obtained from H. perforatum (Stojanovic et al, 2013). Thus, a number of Hypericum species from different countries of the world, such as Brazil (França et al, 2013), Greece (Mathioudaki et al, 2018), Italy (Mandrone et al, 2017), Tunisia (Hosni et al, 2017), Serbia, Montenegro (Zdunic et al, 2017), Portugal (Nogueira et al, 2008), Lithuania (Bagdonaite et al, 2010), Jordan (AI-Rifaee et al, 2010), Iran (Pirbalouti et al, 2014), Peru (Ccana-Ccapatinta et al, 2014, and Turkey (Cirak et al, 2016a(Cirak et al, , 2016b(Cirak et al, , 2017a(Cirak et al, , 2017b have been investigated in respect to the presence of chemical ingredients that give health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous studies and publications, Hypericum species are of high-priority research due to the increasing pharmacological significance and commercial value of Hyperici herba, officially obtained from H. perforatum (Stojanovic et al, 2013). Thus, a number of Hypericum species from different countries of the world, such as Brazil (França et al, 2013), Greece (Mathioudaki et al, 2018), Italy (Mandrone et al, 2017), Tunisia (Hosni et al, 2017), Serbia, Montenegro (Zdunic et al, 2017), Portugal (Nogueira et al, 2008), Lithuania (Bagdonaite et al, 2010), Jordan (AI-Rifaee et al, 2010), Iran (Pirbalouti et al, 2014), Peru (Ccana-Ccapatinta et al, 2014, and Turkey (Cirak et al, 2016a(Cirak et al, , 2016b(Cirak et al, , 2017a(Cirak et al, , 2017b have been investigated in respect to the presence of chemical ingredients that give health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The following binary gradient elution program was used: 0-1 min (B 5→5%), 1-14 min (B 5→20%), 14-20 min (B 20→80%), 20-30 min (B 80→100%), 30-39 min (B 100→100%), 39-39.5 min (B 100→5%), 39.5 -45 min (B 5-5%). The mobile phase was delivered with a flow rate of 1.0 mL min -1 ; volume of extract injected was 10 µL (Cirak et al, 2016). Detection was performed at 210-790 nm wavelength range with a constant column temperature at 40 o C. The eluted compounds were identified on the basis of their retention time by comparison with retention time of reference standards and also confirmed with UV spectra's of reference standards in the wavelength range from 210 to 790 nm.…”
Section: Preparation Of Plant Extracts and High-performance Liquid Chmentioning
confidence: 99%
“…20,21 In the present study, it was found that the considerable amount of the phenolic compounds in H. pseudolaeve consisted of the flavonoids, corroborating the previous reports on other Hypericum species. [22][23][24][25][26] Wound healing and anti-depressant activities of the members of this genus have been associated with phenolic compounds such as hyperoside and epicatechin in some of the previous studies. 11,27 Therefore, phenolic content is important for the biological activies of Hypericum sp.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%